Digital Competence among EFL Teachers: A Review of Challenges and Developmental Needs (مجلة الفاروق للعلوم, 2026)
This literature review examines digital competence among English as a Foreign Language teachers (EFL), focusing on its conceptual foundations, challenges, developmental needs, improvement strategies, and changing teacher roles in digital education. The review highlights that digital competence extends beyond basic technical skills to include the ability to select, evaluate, create, and integrate digital technologies effectively, critically, ethically, and pedagogically. The literature identifies several factors that may hinder EFL teachers’ digital competence, including limited technological knowledge, insufficient professional training, low confidence, inadequate infrastructure, time constraints, difficulties in integrating technology with language pedagogy, and the rapid development of emerging technologies. The increasing use of artificial intelligence has further expanded teachers’ professional responsibilities and created new needs related to AI literacy, ethical awareness, data privacy, and academic integrity. The review also emphasizes that EFL teachers increasingly function as learning facilitators, designers of digital learning experiences, managers of online environments, digital assessors, and guides for responsible technology use. To address existing challenges, the study recommends continuous professional development, EFL-specific digital training, practical experience, collaborative learning, reflective practice, AI literacy, and strong institutional support. Overall, digital competence should be viewed as a continuous process of professional growth that enables EFL teachers to adapt to technological change and enhance language teaching and learning in contemporary educational contexts across diverse educational settings.